2020
DOI: 10.1080/17446651.2020.1720511
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota: a promising target against cardiometabolic diseases

Abstract: Introduction: Cardiometabolic diseases (CMD) are a group of interrelated disorders such as metabolic syndrome, type 2 diabetes mellitus and cardiovascular diseases (CVD). As the prevalence of these diseases increases globally, efficient new strategies are necessary to target CMD and modifiable risk factors. In the past decade, evidence has accumulated regarding the influence of gut microbiota (GM) on CMD, providing new targets for therapeutic interventions. Areas covered: This narrative review discusses the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 168 publications
0
26
0
Order By: Relevance
“…As discussed, the microbiome is the central determinant for TMAO generation [135]. The TMAO precursor, TMA, is generated microbiologically within the intestine, and antibiotics were shown to suppress TMAO formation [94,115,136].…”
Section: Tmao Variability By Microbiome Variabilitymentioning
confidence: 99%
“…As discussed, the microbiome is the central determinant for TMAO generation [135]. The TMAO precursor, TMA, is generated microbiologically within the intestine, and antibiotics were shown to suppress TMAO formation [94,115,136].…”
Section: Tmao Variability By Microbiome Variabilitymentioning
confidence: 99%
“…Changes in gut microbiota composition have been related to a wide variety of metabolic events such as an increase in adiposity, dyslipidaemia and T2DM. These disorders bring about an increased gut permeability, disrupting bile acid metabolism, serum levels of lipopolysaccharide and affecting SCFA production and function [ 141 ].…”
Section: Gut Microbiota In Diabesitymentioning
confidence: 99%
“…Thus, it has become increasingly apparent that certain gut microbialderived metabolites, such as some bile acids, short-chain fatty acids, and trimethylamine-N-oxide, may contribute to CVD development and progression. [3][4][5][6][7][8][9][10][11] The topic has attracted much attention as it can be deduced by the extraordinary number of review articles that can be found in a wide variety of scientific journals. Furthermore, new findings and discoveries in this area, such as the recent identification of the gut microbial metabolite phenylacetylglutamine and its implication in thrombosis potential and CVD, broaden our view of axis diet-microbiota-CVD.…”
Section: Introductionmentioning
confidence: 99%